Digitalization in educational administration: Enhancing efficiency and overcoming challenges in school management - Saryanto, Saryanto; Najib, Khotim Hanifudin; Nalle, Christina (Universitas Jambi, Indonesia, 2026)
The digital transformation of educational administration has become an essential strategy to enhance efficiency, transparency, and accountability in school management. This study explores how digitalization impacts administrative performance, identifies key challenges, and highlights opportunities in the implementation process across Indonesian schools. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving school leaders and administrative staff. The findings reveal that digital systems improve data accessibility, reduce administrative workload, and support decision-making. However, issues such as limited digital literacy, infrastructure gaps, and resistance to change remain significant barriers. The study emphasizes the importance of human resource readiness, supportive policies, and technological infrastructure to ensure successful digital integration. It concludes by offering strategic recommendations for policy makers and educational leaders to foster sustainable digital ecosystems in school administration. This research contributes to the discourse on educational reform through digital innovation in developing country contexts.